Potensi Dan Pengembangan Mahakam Riverside Market Melalui Community-Based Tourism - Lutviani Silvia Fitri; I Komang Astina; Akmal Fahmi (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2022)
The existence of Mahakam Riverside Market (MARIMAR) as a forum that aims to improve theeconomy in Samarinda City becomes a very interesting object and has the potential to become a newtourist attraction in Samarinda City. MARIMAR has had both positive and negative impacts on society.The resulting positive impacts include increasing the economy and public welfare. However, on theother hand, the opening of tourism like this certainly has a negative impact such as environmentaldamage, air pollution and a decrease in water and environmental quality. This study aims to analyzethe Mahakam Riverside Market (MARIMAR) development strategy through community-based tourism(CBT). This research is a qualitative descriptive research with a naturalistic research design. The dataanalysis used is Tourism Component Analysis 4A and SWOT Analysis. The results of the analysis showthat Mahakam Riverside Market (MARIMAR) has strong potential to be developed into a tourist areathrough local community empowerment (CBT). Empowerment of local communities can be done in 3stages, namely enabling (capacity building), empowering, and protecting (maintaining).Keyword: Mahakam Riverside Market; community-based tourism; Mahakam River; Samarinda